Epidemiological Profile of Scorpion Sting Accidentes in Anápolis- GO, 2020-2025 (CIPEEX, 2025)
BACKGROUND: Scorpion sting accidents remain a significant public health issue in Brazil, with over 60% of cases occurring in rural areas¹. In Anápolis, Goiás, a municipality with notable urban and rural populations, 463 cases were reported from 2020 to 2025². These incidents can progress to severe clinical conditions if not properly treated, underscoring the need to understand their epidemiological profile to enhance healthcare delivery³. OBJECTIVE: To analyze the epidemiological profile of scorpion sting accidents in Anápolis, focusing on time to medical care, victims’ educational level, and clinical outcomes. METHODS: An observational, descriptive, retrospective study based on secondary data from Brazil’s Ministry of Health DataSUS system, examining the relationship between educational level, time to seek medical care, and outcomes of cases reported from 2020 to 2025 in Anápolis, Goiás, Brazil. RESULTS: Of the 463 cases, 33.7% of victims had completed secondary education, 10% incomplete secondary, 31.5% incomplete primary, 5.6% complete primary, 6.2% completed higher education, 1% incomplete higher education, and less than 1% were illiterate. The highest proportions were among those with completed secondary and incomplete primary education. Regarding time to medical care, 27% sought care within the first hour, 35% within 3 hours, and the remainder after 3 hours, often exceeding the ideal 2-hour window⁶. Nevertheless, 461 cases (99.6%) resulted in recovery, with two deaths reported (one at 0-1 hour, another at 1-3 hours)⁴. CONCLUSION: Scorpion sting accidents affect individuals across educational levels, with higher incidence among those with completed secondary and incomplete primary education, showing no significant impact on time to seek care, even when comparing rural (lower education) and urban (higher education) areas. Socioeconomically vulnerable populations may face greater risk, possibly due to limited healthcare access⁵. Time to medical care was not the primary determinant of outcomes, as most cases resulted in recovery, but the deaths suggest the need for further studies on clinical and social factors influencing outcomes.
Keywords: scorpion sting accidents; epidemiological profile; Anápolis; Goiás